The physiological stress response of juvenile nurse sharks (Ginglymostoma cirratum) to catch-and-release recreational angling. - Katherine C Giesy; Jacob Jerome; Julia Wester; Evan D'Alessandro; M Danielle McDonald; Catherine Macdonald (PLoS ONE)
Nurse sharks (Ginglymostoma cirratum), especially juveniles, are often encountered by near-shore and shore-based recreational anglers and are suggested to exhibit minimal behavioral and physiological responses to capture, largely based on studies of adults using commercial or scientific fishing methods. To quantify the sub-lethal effects of recreational angling on juvenile nurse sharks, 27 individuals (across 31 angling events) were caught using hook-and-line fishing methods. Over a 30-min period, 4 blood samples were taken with variable time intervals between sampling (i.e., randomized ordering of an interval of 5, 10, and 15 min between each sampling event). Lactate increased by 611% (6.7 ± 2.17 mmol/L) on average over the 30-min fight, and significant relationships were identified between lactate and blood draw number, fight time, and temperature, with large effect sizes. Significant relationships were also detected between blood draw number, glucose, and hematocrit, while osmolality was only affected by fishing site. These results suggest juvenile nurse sharks may exhibit a greater physiological stress response when exposed to recreational angling than adults captured with other fishing methods.